Virtual Water Flows in the EU27: A Consumption‐based Approach. (19th May 2016) - Serrano, Ana; Guan, Dabo; Duarte, Rosa; Paavola, Jouni
Summary: The use of water resources has traditionally been studied by accounting for the volume of water removed from sources for specific uses. This approach focuses on surface and groundwater only and it ignores that international trade of products with substantial amounts of embodied water can have an impact on domestic water resources. Using current economic and environmental data, we conduct a consumption‐based assessment of virtual water flows in the European Union (EU27). We find that the total water footprint (WF) of 2, 280 cubic meters (m 3 ) per capita for the EU27 mostly consists of green water use (precipitation stored as soil moisture), which is omitted in the conventional water accounting. Blue water (surface and groundwater.) and gray water use (the volume of freshwater needed to dilute pollutants to meet the applicable water quality standards), which are targeted by current EU water policies, only make up 32% of the total WF. We also find that Europeans imported 585 cubic kilometers (km 3 ) (10 9 m 3 ) of virtual water, or around 28% of global virtual water trade flows, in 2009. Within Europe, Germany is a key net importer of water through the trade of products in agriculture, the food industry, the chemical sector, and electricity generation. Countries in Southern and Eastern Europe have specialized in water‐intensive agriculture and are key exporters of virtual water despite experiencing physical scarcity of water. Our results suggest that there is a need to reconsider water policy in the EU to address water transfers occurring through trade and to grasp the interlinkages between green, blue, and gray water—which are likely to become more important in water‐scarce parts of Europe, with a changing climate.